Dupilumab Improves Histopathologic Features in Patients With Eosinophilic Esophagitis: LIBERTY EoE TREET Study Results - Margaret H. Collins; Marc E. Rothenberg; Evan S. Dellon; Albert J. Bredenoord; Ikuo Hirano; John Leung; Xian Sun; Lila Glotfelty; Arsalan Shabbir (Gastro Hep Advances, 2025)
Background and Aims: This post hoc analysis assessed the effect of dupilumab on the individual components of the Eosinophilic Esophagitis Histology Scoring System (EoEHSS) and the relationship between histopathologic and endoscopic measures in the LIBERTY eosinophilic esophagitis (EoE) TREET population. Methods: The analysis included patients who received dupilumab 300 mg weekly (qw) or placebo for 24 weeks (Parts A and B). Eligible patients who completed Parts A or B entered Part C and received dupilumab 300 mg qw for 28 weeks (week 52). Changes from baseline to week 24 and week 52 in the EoEHSS grade/stage components were assessed. Associations between histopathologic, symptomatic, and endoscopic features were evaluated using Spearman correlation. Results: At week 24, dupilumab improved most EoEHSS grade/stage component scores vs placebo. These improvements were sustained at week 52 in patients continuously on dupilumab; patients who switched from placebo to dupilumab at week 24 improved EoEHSS grade/stage component scores at week 52 to levels similar to those observed in patients continuously on dupilumab. Dupilumab also increased the proportion of patients in remission at week 24 vs placebo, with further increases at week 52, as assessed by the EoE histology remission score. EoEHSS grade and stage total scores correlated strongly with peak eosinophil count (PEC), moderately to strongly with Endoscopic Reference Score, and weakly with Dysphagia Symptom Questionnaire score. Several EoEHSS grade/stage component scores correlated strongly with PEC but not with Dysphagia Symptom Questionnaire scores. Conclusion: Dupilumab 300 mg qw improved histopathologic measures of EoE beyond PEC at week 24, with improvements sustained to week 52 (Video 1).